THE USE OF REDW (READ, EXAMINE, DECIDE, WRITE) STRATEGY TO IMPROVE READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMP NEGERI 1 GAUNG ANAK SERKA - ', Sartika; Syarfi, M; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research is aimed to describe and to investigate whether Read, Examine, Decide, Write strategy can increase the ability of SMP Negeri 1 Gaung Anak Serka in reading comprehension ability. The participants were 30 students of the second year students SMP Negeri 1 Gaung Anak Serka. The data collection technique consisted of observation, field note, and tests. The research findings can be briefly explained as follows. First, the students reading ability could be improved by using Read, Examine, Decide, Write strategy. Before the research was done, the average score of the students reading ability was only 54.7. After the research one for cycle 1, it improved to 63.2. Cycle 2, it increased up to 70.2. Second, the students’ awareness in comprehending the texts. Read, Examine, Decide, Write strategy can improve students’ reading ability. Third, the teacher was able to apply Read, Examine, Decide, Write strategy to make the teaching process effective and it also helped students improve their reading comprehension ability and more active in learning process.Keywords: Strategy Read, Examine, Decide, Write, students improve treadingcomprehension ability. Text Descriptive.